2020
DOI: 10.21203/rs.3.rs-44045/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hsa_circ_0001944 promotes the growth and metastasis in bladder cancer cells by acting as a competitive endogenous RNA for miR-548

Abstract: Background: Bladder cancer (BC) is a common genitourinary malignancy worldwide. Circular RNAs (circRNAs) participate in cancer development, including BC; thus, the roles of circRNAs in this process have attracted significant attention. Methods: In this study, high-throughput sequencing was used to analyze circRNA expression profiles in BC tissues. We performed RT-qPCR to determine hsa_circ_0001944 expression in BC tissues. We used fluorescence in situ hybridization (FISH) to detect hsa_circ_0001944 expression … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
(20 reference statements)
1
11
0
Order By: Relevance
“…14 In addition, high circ_0001944 expression facilitated bladder cancer advancement by upregulating PROK2 via sponging miR-548. 13 Therefore, we concluded that circ_0001944 played a promoting effect on cell tumor growth and glycolysis in NSCLC.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…14 In addition, high circ_0001944 expression facilitated bladder cancer advancement by upregulating PROK2 via sponging miR-548. 13 Therefore, we concluded that circ_0001944 played a promoting effect on cell tumor growth and glycolysis in NSCLC.…”
Section: Discussionmentioning
confidence: 88%
“…Circ_0001944 had been uncovered to exert a promoting influence on the tumorigenesis of bladder cancer. 13 Moreover, circ_0001944 was highly expressed in NSCLC tissues. 14 At present, the role of circ_0001944 in NSCLC has not been verified.…”
Section: Introductionmentioning
confidence: 99%
“…Physiologically, a previous study [37] reported that dominant isoforms of gene FIRRE transcription product was circular, with merely minor linear FIRRE transcript during human embryonic stem cell differentiation. Pathologically, circFIRRE was prominently upregulated and promoted the progression and multiple organ metastases of multiple carcinomas [38][39][40], including bladder cancer, breast cancer and non-small cell lung cancer (NSCLC). These results suggest that the increased proportion of circFIRRE in transcriptional outputs may be universal.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs have recently been shown to be involved in neuronal development, regulation of cellular function, immune regulation, pathogenesis of heart failure, and the development of diabetes [9][10][11][12]. Certain types of circRNAs have been found to be significantly dysregulated in gastric cancer, bladder cancer, and triple-negative breast cancer, and these deregulated circRNAs are thought to be involved in the development of cancer [13][14][15]. These findings indicate that circRNAs may become a new type of potential biomarker and therapeutic target for cancer; however, clarifying the dysregulated circRNAs and identifying their functions are still an ongoing process in cancer research.…”
Section: Introductionmentioning
confidence: 99%